MODEL PEMBELAJARAN MAKE A MATCH BERMEDIA KARTU BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK AUTIS DI SLB - Nurmala Aprilina, Fenda (Jurnal Pendidikan Khusus, 2017)
ABSTRACT  Children with autism grade 1 and grade 2 in SLB Mutiara Hati Sidoarjo can not read well. When taught to read simple sentences the child can only mention the letter A-Z. Children need to be guided so that they can mention the letter A-Z, spell the letters into syllables spelling syllables into words and connect words into sentences so that children can improve the ability to read the beginning in accordance with the teaching materials. The purpose of this study is to prove the influence of learning model make a match card pictorial media to the ability to read the beginning of children with autism in SLB Mutiara Hati Sidoarjo. This research uses quantitative quantitative and pre-experimental research type, using One Group research design, pretest, post test design. The results showed a significant influence, seen from the ability of the child through the aspects of mentioning the letter A-Z, spelling letters into syllables, spelling syllables into words, and connect words into sentences. This is evidenced by the results of data analysis that shows the value of z arithmet = 2.20 is greater than the value of z table = 1.96, which means the influence of learning model make a match with picture card media on the ability to read the beginning of children with autism in SLB Mutiara Hati Sidoarjo. Keywords: Make a Match, picture card media, start reading capability